(untitled) (Development Service Industry Management, 2025)
The study focuses on analyzing the impact of digital marketing on shaping demand for pellet heating equipment in Ukraine. The relevance of the topic is determined by the growing importance of renewable energy sources and the need for energy independence under martial law and energy market instability. Pellet heating is considered one of the most economically viable and accessible solutions, particularly for small and medium-sized enterprises. At the same time, increasing competition between domestic and foreign manufacturers highlights the need to identify effective promotion channels. The research emphasizes the decisive role of the digital environment, which has become the main platform for consumer interaction. Modern buyers aim to obtain comprehensive online information, including technical specifications, installation instructions, customer reviews, and video demonstrations. This shift reduces the importance of traditional offline exhibitions, redirecting efforts toward digital tools. The findings reveal that the most effective customer acquisition channels are YouTube, organic search, and paid search advertising, while marketplaces (Rozetka, Epicenter Online, Prom.ua) play a supportive role in the sales funnel thanks to strong SEO visibility and enhanced brand trust. The corporate website is identified as the central element of the communication strategy, as it ensures the conversion of consumer interest into concrete actions such as inquiries or purchases. In contrast, social networks, display advertising, and external links show low efficiency in this industry. The scientific novelty of the study lies in the lack of specialized research systematically analyzing digital promotion channels in the pellet heating equipment segment. The practical significance of the results is in identifying the most effective digital marketing tools that allow companies to optimize budgets, strengthen competitiveness, and accelerate the adoption of modern autonomous and energy-efficient heating systems in the Ukrainian market.